113 IMPACT OF DELIVERY ROOM CARDIOPULMONARY RESUSCITATION ON AGE AT THE TIME OF DEATH IN INFANTS < 1, 200 GRAMS. (1st January 2006) - Castillo, A.; Deulofeut, R.; Sola, A.
Abstract : Background: Delayed mortality may be associated with prolonged suffering and also with emotional, economic, and resource costs. The age at the time of death in extremely low birth weight infants (ELBW) is widely variable. The influence on this variability of delivery room cardiopulmonary resuscitation (DR-CPR) has not been investigated. Objective: To analyze if the age at the time of death in infants < 1, 200 g is different in those who received DR-CPR compared to those who died but did not require DR-CPR. Design/Methods: Analysis of all infants < 1, 200 g who died and had been born at two Emory perinatal centers in the last 5 years (1/2000-12/2004). Exclusion criteria were major congenital malformations and provision of only comfort care. DR-CPR was defined as chest compression and/or epinephrine use in the delivery room (DR). Demographics included Apgar score, gestational age, gender, prenatal steroids, multiple pregnancies, mode of delivery, age at time of death and others. Comparisons by chi square, Fisher's, Student t, and RR when appropriate (whole group and BW specific). Results: A total of 87 infants < 1, 200 g who died met enrollment criteria; 26 of them (30%) received DR-CPR. Of the 87 infants, 25% died in first day (d); 18% at 1-3 d; 5% between 4 and 7 d; 29% between 8 and 28 d, and 23% > 28 d of age. The DR-CPR group was similar to the no DR-CPR group in birth weight (726 6 160 vs 731 6 176) and gestational age (24.8 6 1.9 vs 25.3 6 2.2). The average length of stay (ALOS) was widely variable (21.8 6 47 vs 30.7 6 56.9; p = .669). Death in the DR (27% vs 0%; p = .000), in the first 12 hours of life (38% vs 7%; p = .001) and in the first day (42% vs 20%; p = .047) was more frequent in the DR-CPR group. Death after 28 d was 11.5% in DR-CPR vs 26.6% in no DR-CPR infants (p = .2); and the median length of stay for these infants was 156.00 d vs 41.00 d, respectively. Conclusion: A large proportion of the infants < 1, 200 g who die do so after many days in the hospital. Exposure to DR-CPR is associated with a higher proportion of early mortality. However, infants exposed to DR-CPR who survive > 28 days die after a prolonged length of stay. It remains to be determined if criteria can be identified to avoid delaying the inevitable.